Study on the Failure Mechanism of Lower Cambrian Shale under Different Bedding Dips with Thermosolid Coupling. (26th March 2022) - Wang, Wentao; Wu, Zhonghu; Song, Huailei; Cui, Hengtao; Lou, Yili; Tang, Motian; Liu, Hao
Abstract : To investigate the damage pattern and acoustic emission pattern of temperature on laminated shales, numerical experiments were carried out using the RFPA2D-Thermal numerical software under the effect of thermosolid coupling. During the tests, temperatures of 30°C, 60°C, and 90°C were controlled, and five sets of shales containing different laminar dips were numerically modeled at each temperature, with dips of 0°, 22.5°, 45°, 67.5°, and 90°. The test results show that (1) the increase in temperature reduced the linear elastic phase of the shale specimens in each group, with a significant reduction in the linear elastic phase of the shale at lamina dips of 22.5° and 45°. (2) The lamination effect decreased slightly as the temperature rose from 30°C to 60°C, and the most significant enhancement of the lamination effect on the shale occurred when the temperature reached 90°C. (3) The shale damage pattern is divided into five types (N, ʌ, v, slanted I-type, and cluttered-type), in which the lamina effect is stronger for high-angle lamina dips, and the lamina surface has a strong dominant effect on the entire shale crack expansion. At a temperature of 90°C, the lamina effect and temperature effect of the shale reached their maximum at the same time, and the thermal and load stresses inside the shale acted together causing the shale to show a complex damage mode. (4) The fractal dimension was used to analyze the damage pattern of the shale. The larger the fractal dimension was, the greater the crack rate of the specimen. The fractal dimension curve was flatter at a temperature of 60°C, while at 90°C, the fractal dimension rose rapidly, indicating the most favorable crack expansion in the shale at a temperature of 90°C.